2018
DOI: 10.1177/1475090218810248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of roll dynamics of an autonomous underwater vehicle

Abstract: This article aims to identify the roll channel parameters of an autonomous underwater vehicle. These parameters include hydrodynamic coefficients, motor torque, eccentricity, misalignments and mounting imperfections. In the proposed method, an approximation of the hydrodynamic coefficients is made at first via semi-empirical methods. In the next step, a proportional–integral–derivative controller is designed with respect to the approximated coefficients. Since the approximations can be very uncertain, the robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In this section, the parameter identification method is designed for the system equations of the previous subsection. There are more methods for parameter identification; for example, the least squares method and the maximum likelihood method [42]. In contrast to these two methods, neural networks with nonlinear mapping capability are selected to identify the parameter of this system.…”
Section: Rnn Structurementioning
confidence: 99%
“…In this section, the parameter identification method is designed for the system equations of the previous subsection. There are more methods for parameter identification; for example, the least squares method and the maximum likelihood method [42]. In contrast to these two methods, neural networks with nonlinear mapping capability are selected to identify the parameter of this system.…”
Section: Rnn Structurementioning
confidence: 99%
“…2 Among other fields, research has been carried out on their operations and deployment and recovery systems, 3 as well as the system of control 4 and fault detection, 5 using predictive models for the control of this type of vessel 6 or identifying the parameters of the balancing channel, including hydrodynamic coefficients, motor torque, eccentricity, misalignments and mounting imperfections. 7 Other current research also focuses on the study of topics such as the path tracking control methodologies, 8 the structural design, 9 the study of the flow around the hull of the vehicle 10 or multi-objective optimization of the design of the submarine’s hull shape, 11 with the aim of reducing the energy consumption, the construction of testing scenarios 12 and the development of new technologies, such as the use of multi-sonar controllers. 13…”
Section: Introductionmentioning
confidence: 99%
“…Using LS method, in Petrich et al, 18 dynamics of the dive plane of Virginia Tech 475 AUV was identified. In Abtahi et al, 19 an offline method was developed to identify the roll dynamics of an AUV. In Yan et al, 20 a recursive subspace identification method was developed and simulated for an AUV.…”
Section: Introductionmentioning
confidence: 99%